Clinical Research Primer for Medical Students: Behind the Curtain, a Framework on Peer Review for Trainees - Niznik, Taylor; Tavakol, Sherwin A.; Stephens, Tressie; Bauer, Andrew M.; Dunn, Ian F.; Graffeo, Christopher S. (Journal of Neurological Surgery Reports, 2025)
Academic scholarship is an increasingly emphasized component of undergraduate medical education (UME), in particular since the USMLE Step 1 examination transitioned to a pass/fail grading scheme in 2022. Peer review is a cornerstone of academic publishing, but essentially no formal training exists at the UME or graduate medical education levels to prepare trainees for participation in the process as authors or reviewers. This clinical research primer presents an introductory set of guidelines and pearls to empower trainee participation in the peer-review process as both authors and reviewers. We outline a systematic approach to manuscript evaluation and recommend a nonlinear strategy that begins with the Abstract and Methods, followed by Figures, Tables, and Results, concluding with the Discussion. This framework includes guidelines for constructing effective reviews, from initial summary and overall recommendations to specific, actionable comments. Participation in peer review can also advance trainees' scholarly development by exposing gaps in literature that inspire new research questions and developing their ability to anticipate and address potential reviewer critiques in their own manuscript preparation. While initial implementation requires close supervision from experienced mentors, this structured approach streamlines the peer-review learning process and provides substantial benefits for all participants in academic publishing, enhancing both mentorship relationships and scholarly development.
Keywords: peer review; education; medical student; UME; GME